Analisis Nilai Ekspor Nikel Kode HS 75 Tahun 2017-2023 Dengan Pendekatan Error Correction Mechanism (ECM) - Rahman, Faiz Fathur; Pasaribu, Ernawati (Seminar Nasional Official Statistics, 2024)
Nickel ore is a highly potential mining commodity, evidenced by the fact that 52 percent of the world's nickel reserves are located in Indonesia, and in 2021, Indonesia became the largest nickel producer globally. However, the processing of nickel in Indonesia remains suboptimal, given the substantial volume of nickel ore exported without processing. Therefore, this study aims to analyze the impact of investment, production, unit cost, RCA value, and ECI on the export value of Indonesia's nickel. This research employs the Error Correction Mechanism (ECM) method. The analysis results indicate that, in the long term, nickel ore production, unit cost, and RCA have a significant positive effect. In the short term, only RCA and ECI have a significant positive effect on the export value of nickel. Lastly, according to the speed of adjustment value, the short-term model will be corrected by 44.78 percent in the first year and the remaining in subsequent years.